Acute kidney injury requiring dialysis and in‐hospital mortality in patients with chronic kidney disease and non–ST‐segment elevation acute coronary syndrome undergoing early vs delayed percutaneous coronary intervention: A nationwide analysis. Issue 12 (20th December 2017) - Patel, Brijesh; Carson, Philip; Shah, Mahek; Garg, Lohit; Agarwal, Manyoo; Agrawal, Sahil; Arora, Shilpkumar; Steigerwalt, Susan; Bavry, Anthony; Dusaj, Raman; Patel, Nainesh; Feldman, Bruce
Abstract : Background: Chronic kidney disease (CKD) is a well‐known risk factor for coronary artery disease and is associated with poor outcomes following an acute coronary syndrome (NSTE‐ACS). The optimal timing of an invasive strategy in patients with CKD and NSTE‐ACS is unclear. Hypothesis: Timing of PCI in CKD patients will not affect the risk of mortality or incidence of dialysis. Methods: We queried the National Inpatient Sample database (NIS) to identify cases with NSTEMI and CKD. Patients who underwent percutaneous coronary intervention (PCI) day 0 or 1 vs day 2 or 3 after admission were categorized as early vs delayed PCI, respectively. The primary outcomes of the study were in‐hospital mortality and acute kidney injury requiring hemodialysis (AKI‐D). The secondary outcomes were length of stay and hospital charges. Baseline characteristics were balanced using propensity score matching (PSM). Results: After PSM, 3708 cases from the delayed PCI group were matched with 3708 cases from the early PCI group. The standardized mean differences between the 2 groups were substantially reduced after PSM. All other recorded variables were balanced between the 2 groups. In the early and delayed PCI groups, the incidence of AKI‐D (2.5% vs 2.3%; P = 0.54) and in‐hospital mortality (1.9% vs 1.4%; P = 0.12) was similar. Hospital charges and length of stay were higher in the delayed PCI group. Conclusions: The incidence of AKI‐D and in‐hospital mortality among patients with CKD and NSTE‐ACS were not significantly affected by the timing of PCI. However, delayed PCI added significant cost and length of stay. A prospective randomized study is required to validate this concept.